Profil Pengajaran Guru Matematika Madrasah Tsanawiyah terhadap Pengelolaan Kelas pada Materi Bentuk Aljabar - Amelia, Virda Fitri; Pandora, Misyel; Febyanti, Adinda Isna Febyanti Isna; Rofiki, Imam (ARITHMETIC: Academic Journal of Math, 2024)
Effective classroom management can improve the quality of learning. However, there are still problems in teaching mathematics teachers related to classroom management, especially in teaching algebraic material. Therefore, this research aims to describe the teacher's teaching profile regarding mathematics classroom management in algebraic forms material. The type of research used was a descriptive study using a qualitative approach through data collection using observation, interview, and documentation techniques. The participants of this research were one mathematics teacher and 30 grade 9 students at MTsN 1 Kota Malang. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. The results of this research show that the teacher's teaching has implemented a student-centered learning approach and supports good classroom management. Teachers have been able to implement Technological Pedagogical and Content Knowledge (TPACK) in teaching and classroom management for effective learning. Therefore, the results of this research can contribute to knowledge regarding technology-based mathematics classroom management for students.